Street Children Religious Education: A Study on Car Window Cleaning Kids in Jambi - Asad Isma; Muhammad Junaidi HB (AT-TA'LIM, 2018)
Children begin careers on the streets in several locations in the city of Jambi. They work on the streets as street musicians, vehicle glass cleaners, newspaper and tissue sellers, both forcibly and deliberately. Their existence is influenced by some factors, such as family neglect and socio-economic conditions; as well as finding work on the streets and sustaining the work are much easier than looking for work which uses energy or mind. The purpose of this research is to study the religious education of street children who become car glass cleaners which has increased significantly compared to other street professions. This study aims to explore two issues: where the children obtain their religious education and to what extent they practice it in their daily life. Qualitative collecting data techniques were used including observation and interviews. This research found that the street children interviewed in this study only had access to religious education at morning school. They do not attend madrasah, the Qur'an educational school or Taman Pengajian Alquran (TPA), and Sekolah Islam Terpadu. The dominant factors affecting their religious education were their school and their peer group at school. Meanwhile, parents seldom practice the religious duty in family, thus the parents’ influence on the children’s religious practices was minimal. Therefore, this research recommends other actors give early religious education for street children. Religious education can be integrated with their shelter homes which can be their early Islamic religious education.